Characterization of a two‐dimensional liquid‐filled ion chamber detector array used for verification of the treatments in radiotherapy. Issue 5 (14th April 2014) - Markovic, Miljenko; Stathakis, Sotirios; Mavroidis, Panayiotis; Jurkovic, Ines‐Ana; Papanikolaou, Nikos
Abstract : Purpose: : The purpose of the study is to investigate the characteristics of a two‐dimensional (2D) liquid‐filled ion chamber detector array, which is used for the verification of radiotherapy treatment plans that use small field sizes of up to 10 × 10 cm. Methods: : The device used in this study was Octavius 1000 SRS model (PTW, Freiburg, Germany). Its 2D array of detectors consists of 977 liquid‐filled ion chambers arranged over an area of 11 × 11 cm. The size of the detectors is 2.3 × 2.3 × 0.5 mm (volume of 0.003 cm 3 ) and their spacing in the inner area of 5.5 × 5.5 cm is 2.5 mm center‐to‐center, whereas in the outer area it is 5 mm center‐to‐center. The detector reproducibility, dose linearity, and sensitivity to positional changes of the collimator were tested. Also, the output factors of field sizes ranging from 0.5 × 0.5 to 10 × 10 cm 2 both for open and wedged fields have been measured and compared against those measured by a pin‐point ionization chamber, liquid filled microchamber, SRS diode, and EDR2 film. Results: : Its short‐term reproducibility was within 0.2% and its medium and long‐term reproducibility was within 0.5% (verified with air ionization chamber absolute dose measurements), which is an excellent result taking into account the daily fluctuation of the linear accelerator and the errors in the device setup reproducibility. The dose linearity and dose rate dependence were measured in the range of 0.5–85 Gy and 0.5–10 Gy min −1, respectively, and were verified with air ionization chamber absolute dose measurements was within 3%. The measurements of the sensitivity showed that the 2D Array could detect millimetric collimator positional changes. The measured output factors showed an agreement of better than 0.3% with the pinpoint chamber and microliquid filled chamber for the field sizes between 3 × 3 and 10 × 10 cm 2 . For field sizes down to 1 × 1 cm 2, the agreement with SRS diode and microliquid filled chamber is better than 2%. The measurements of open and wedge‐modulated field profiles were compared to the film and ionization chamber in water measurements. Conclusions: : The Octavius Detector 1000 SRS is an accurate, precise, and reliable detector, very useful for the daily performance of the patient specific quality assurance of radiotherapy treatment plans.